The Evolution of Islamic Philanthropy in Indonesia’s Digital Age (2016–2023) - Ridho, Hilmi; Sodiqin, Ali; Mujib, Abdul (Al-Ahkam, 2025)
Zakat management institutions have changed the method of collecting Islamic philanthropic funds (zakāt, infāq, ṣadaqah [ZIS]) from conventional to digital by utilizing digital platforms. This article aims to describe the transformation by the National Board of Zakat Republic of Indonesia (BAZNAS RI) and the views of scholars regarding the expansion of the meaning of mustaḥiq in the Indonesian context. This research is a normative-empirical legal research with primary data from interviews and secondary data referring to the BAZNAS RI annual report for 2016-2025. After being collected, the data was analyzed using interpretation and description techniques. The results of this study indicate that digital ZIS collection has increased with an average growth of 32%, and its distribution has increased by an average of 30% per year from 2016 to 2023. Digital ZIS management has also had an impact on the expansion of the meaning of the five mustaḥiq groups in Indonesia, namely mu'allaf, riqāb, ghārimīn, sabīlillā, and ibn sabīl. Digital ZIS management needs to be socialized massively in the community. In addition, there needs to be a review of the effectiveness of digital-based productive zakat management for the following years. Likewise, extensive research on the meaning of mustaḥiq and zakat objects that have changed.